Soil profile N2O efflux from a cotton field in arid Northwestern China in response to irrigation and nitrogen management - Kuang, Wennong; Wu, Yufeng; Gao, Xiaopeng; Yin, Mingyuan; Gui, Dongwei; Zeng, Fanjiang (Frontiers in Environmental Science, 2023)
It remains uncertain how different N inputs as synthetic fertilizer or manure and irrigation types affect nitrous oxide (N2O) production and effluxes in the subsurface. A field trial was carried out in 2016 to evaluate the impacts of conventional urea, animal manure, and a 50/50 mix of urea and manure on N2O production/effluxes from a cotton (Gossypium hirsutum L.) field under flood or drip irrigation in northwestern China. Soil N2O concentrations were monitored at 5, 15, 30, and 60 cm depths to assess the production and diffusion rates of N2O in the soil profile. The results showed that N2O concentrations in 0-60 cm ranged between 221 and 532 µL L−1 and averaged 344 µL L−1, which was generally lower compared to other studies in the same region. Manure and flood irrigation significantly increased N2O production at 0-5 cm and 5-15 cm, respectively. That is, the effects of nitrogen management and irrigation types on the N2O production of the profile were reflected in the surface layers and subsurface layers, respectively. All N2O production occurred in the 0-15 cm layer, with the 0-5 cm depth contributing 87-100% of the surface emissions. The response discrepancy of N2O production/diffusion to irrigation and nitrogen management in different soil depths should be fully considered in developing agricultural N2O emission reduction measures.